Combined effect of nisin, carvacrol and a previous thermal treatment on the growth of Salmonella enteritidis and Salmonella senftenberg. (August 2013) - Esteban, María-Dolores; Aznar, Arantxa; Fernández, Pablo S; Palop, Alfredo
The aim of this study was to evaluate the combined effect of a previous mild heat treatment (15 min at 55 ℃) with the use of antimicrobials, nisin and carvacrol, on the growth of Salmonella enteritidis and Salmonella senftenberg. Natural antimicrobials, alone or combined with a previous mild heat treatment, affected the growth of these two serovars in Tryptone Soy Broth at 37 ℃. Increasing concentrations of carvacrol had a significant effect on both growth rate and lag phase duration of both strains. The time to reach stationary phase was almost doubled in the case of S. enteritidis when a concentration of 0.77 mM in carvacrol was added. For S. senftenberg the effect was smaller. The effect of nisin and of heat, applied individually, was lower for both microorganisms. A combination of 1.2 µM nisin with 0.77 mM carvacrol significantly delayed the growth of heat treated cells, compared to the control without antimicrobials, showing additive effects.